Sathow's sinners [large type] - Galloway, Marcus (Wheeler Publishing, 2015)
"Ex-lawman Nate Sathow never cared much for the letter of the law. But when he was hired to kill former preacher Frank Waverly, Nate's sense of justice stayed his hand. Now Nate and Frank ride together--an unlikely pair specializing in tracking down escaped outlaws. For their latest job, Nate and Frank must first round up a few men who know their way around trouble. Once gathered, the ragtag souls set their sights on one Casey "Dog Ear" Pescaterro--a depraved killer with a hefty price on his head. There are plenty of rumors about how he got his nickname--each one bloodier than the next. Since breaking out of jail, he has been gathering a posse...for what, nobody knows. Ordinary lawmen are too scared to find out. And now it's up to Sathow and his sinners to put Dog Ear back in his cage" --